Nutrient Contents of the Fresh Pulps and Dried Pulp Cakes of Vitellaria paradoxa of Gulu District, Uganda - Oryema, Christine; Oryem-Origa, Hannington; Roos, Nanna (Pakistan Journal of Nutrition, 2015)
Vitellaria paradoxa Gaertn locally known as ‘Yaa’ in Acholi is a valuable edible indigenous wild fruit in Gulu District, northern Uganda. It is a multipurpose fruit tree and highly favoured by the inhabitants of this district. Its fruit pulps are eaten when fresh and/or made into cakes and dried. This study determined the nutrient compositions of the fresh pulps and dried pulp cakes of V. paradoxa. Laboratory analyses were undertaken to determine the micro and macro nutrients in the samples on fresh (FM) and dry matter (DM) basis following standard procedures and protocols. The potassium, sodium and calcium contents of the fresh pulps on FM basis were, respectively 38, 7.3 and 234 mg/100 g. The contents of zinc (1.00 mg/100 g), Iron (6.8 mg/100 g) and magnesium (92.01 mg/100 g) on FM basis were the highest in the dried pulp cakes compared to the contents in the fresh pulp cakes. The fresh pulps had higher moisture contents (70.50 g/100 g), Fibre (5.95 g/100 g) and Vitamin A (228.30 μg/100 g) contents. Phytates were absent in both fresh and dried pulp cakes on both FM and DM basis. The study revealed appreciable contents of nutrients in both the fresh pulps and dried pulp cakes that can be useful in supplementing nutrition deficiencies. Further studies are recommended to determine availability of the nutrients in the body when consumed.